Workshop on Molecular Dynamics on Parallel Computers : John von Neumann Institute for Computing (NIC) Research Centre, Jülich, Germany, 8-10 February 1999 - Esser, Rüdiger (World Scientific, 2000)
Molecular dynamics is a well-established technique for simulating complex many-particle systems in many areas of physics, chemistry, and astrophysics. The huge computational requirements for simulations of large systems, especially with long-range forces, demand the use of massively parallel computers. Designing efficient algorithms for these problems is a highly non-trivial task. This book contains the invited talks and abstracts presented at a conference by more than 100 researchers from various fields: computer science, solid state physics, high energy physics, polymers, biochemistry, granular materials and astrophysics. Most of the contributions have been written by users of massively parallel computers and deal with practical issues, but there are also contributions tackling more fundamental algorithmic problems.